Human T-Lymphotropic Virus type 1 infection in an Indigenous Australian population: epidemiological insights from a hospital-based cohort study. (December 2016) - Einsiedel, Lloyd; Woodman, Richard; Flynn, Maria; Wilson, Kim; Cassar, Olivier; Gessain, Antoine
Abstract Background The Human T Lymphotropic Virus type 1 (HTLV-1) subtype C is endemic to central Australia where each of the major sequelae of HTLV-1 infection has been documented in the socially disadvantaged Indigenous population. Nevertheless, available epidemiological information relating to HTLV-1c infection is very limited, risk factors for transmission are unknown and no coordinated program has been implemented to reduce transmission among Indigenous Australians. Identifying risk factors for HTLV-1 infection is essential to direct strategies that could control HTLV-1 transmission. Methods Risk factors for HTLV-1 infection were retrospectively determined for a cohort of Indigenous Australians who were tested for HTLV-1 at Alice Springs Hospital (ASH), 1st January 2000 to 30th June 2013. Demographic details were obtained from the ASH patient management database and the results of tests for sexually transmitted infections (STI) were obtained from the ASH pathology database. Results Among 1889 Indigenous patients whose HTLV-1 serostatus was known, 635 (33.6 %) were HTLV-1 Western blot positive. Only one of 77 (1.3 %) children tested was HTLV-1 infected. Thereafter, rates progressively increased with age (15–29 years, 17.3 %; 30–49 years, 36.2 %; 50–64 years, 41.7 %) reaching 48.5 % among men aged 50–64 years. In a multivariable model, increasing age (OR, 1.04; 95 % CI, 1.03–1.04), male gender (OR, 1.41; 95 % CI, 1.08–1.85), residence in the south (OR, 10.7; 95 % CI, 7.4–15.6) or west (OR, 4.4; 95 % CI, 3.1–6.3) of central Australia and previous STI (OR, 1.42; 95 % CI, 1.04–1.95) were associated with HTLV-1 infection. Infection was acquired by three of 351 adults who were tested more than once during the study period (seroconversion rate, 0.24 (95 % CI = 0.18–2.48) per 100 person-years). Conclusions This study confirms that HTLV-1 is highly endemic to central Australia. Although childhood infection was documented, HTLV-1 infection in adults was closely associated with increasing age, male gender and STI history. Multiple modes of transmission are therefore likely to contribute to high rates of HTLV-1 infection in the Indigenous Australian population. Future strategies to control HTLV-1 transmission in this population require careful community engagement, cultural understanding and Indigenous leadership.